Austenite grain growth and effect of austenite grain size on bainitic transformation. Issue 7 (3rd May 2022) - Mandal, S.; Bhowmik, N.; Tewary, N. K.; Ghosh, P.; Haldar, A.
Abstract : This study was carried out with medium carbon steel to investigate the austenite grain growth kinetics at three temperatures and the effect of prior austenite grain size on bainitic transformation kinetics. Grain growth behaviour of austenite with two initial microstructures, pearlite and bainite, have shown almost similar kinetics. The activation energy values were determined to be 79 and 95 kJ mol −1 for bainitic and pearlitic microstructures, respectively. Prior austenite grain size has shown a strong effect on bainitic transformation kinetics. Higher the austenite grain size faster was the kinetics of bainitic transformation and an increase in the volume fraction of bainitic ferrite. The growth of bainite played the most important role in controlling the bainitic transformation kinetics.